2018
DOI: 10.1053/j.sempedsurg.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Care of infants with gastroschisis in low-resource settings

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 74 publications
0
22
0
1
Order By: Relevance
“…Patients with gastroschisis deteriorate most rapidly due to the large surface area of exposed bowel resulting in hypothermia, hypovolaemia and sepsis, within hours if plastic bowel coverage and resuscitative measures are not instigated at birth. 35 Hence, interventions to improve outcomes must focus on improving resuscitation and timely referral/transportation at the district level, and preintervention resuscitation and perioperative care at paediatric surgery centres. This aligns with recommendations by Kruk et al that to achieve improved outcomes in the SDG era, enhancing access to services must be accompanied by improved quality of care within facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with gastroschisis deteriorate most rapidly due to the large surface area of exposed bowel resulting in hypothermia, hypovolaemia and sepsis, within hours if plastic bowel coverage and resuscitative measures are not instigated at birth. 35 Hence, interventions to improve outcomes must focus on improving resuscitation and timely referral/transportation at the district level, and preintervention resuscitation and perioperative care at paediatric surgery centres. This aligns with recommendations by Kruk et al that to achieve improved outcomes in the SDG era, enhancing access to services must be accompanied by improved quality of care within facilities.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In low-income countries, delays in access to neonatal surgical care and inadequate prehospital management have been reported to be causes of hypothermia, hypovolemia, sepsis, and hydroelectrolytic disorders in patients with gastroschisis. 22 These complications may reflect on postnatal factors, such as contamination and torsion of the vascular pedicle, and result in ischemia and intestinal necrosis, which are lesions typified as complex gastroschisis. 5 , 22 Such serious intestinal injuries were associated with death in patients with gastroschisis in a study carried out in the northern region of the country, whose population was mostly outborn.…”
Section: Discussionmentioning
confidence: 99%
“… 22 These complications may reflect on postnatal factors, such as contamination and torsion of the vascular pedicle, and result in ischemia and intestinal necrosis, which are lesions typified as complex gastroschisis. 5 , 22 Such serious intestinal injuries were associated with death in patients with gastroschisis in a study carried out in the northern region of the country, whose population was mostly outborn. According to the authors, high mortality rates observed by infection and sepsis are probably due to inadequate prenatal care, causing a lack of antenatal diagnosis and leading to inadequate delivery planning, delay in surgical correction (found a mean time of 18.7 h between delivery and wall closure), consequently, increased risk of postoperative infection and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…An international survey reported that only 19% of tertiary pediatric surgery centers in low-income countries had access to parenteral nutrition (13). Wright and colleagues rightfully noted that the challenges to the provision of parenteral nutrition in resource-limited settings include lack of infrastructure and availability of neonate-specific parenteral nutrition bags, difficulty in achieving central venous access and shorter bench life of neonatal parenteral nutrition where available (22). Commencement of enteral feeding was achieved in eight of our patients over an average time of 8 days (median 6 days).…”
Section: Discussionmentioning
confidence: 99%